The "Recreated Experiences" Approach: Exploring the Experiences of Persons Previously Excluded in Research. (10th March 2022) - Noyek, Samantha; Davies, Theresa C.; Batorowicz, Beata; Delarosa, Elizabeth; Fayed, Nora
Individuals with profound motor, communication, and/or cognitive impairments may face difficulties describing subjective or experiential information through (i) speech, (ii) writing using a pencil and paper, and (iii) typing using a standard computer keyboard. Although patient-reported outcome measures and patient-reported experience measures can capture information about this group through proxy-report, we cannot solely rely on the responses of a single proxy for experiential information. Research methods to understand the experiences of individuals with profound motor, communication and cognitive impairments are not well defined in the literature. Purpose: To provide guidance to disability researchers on how to explore the subjective and personal experiences, of individuals with profound, motor, communication, and/or cognitive impairments. Three axes are proposed as important to the structure of the "recreated experiences" method: (i) informants, (ii) data collection methods, and (iii) analyses and reflexivity. Different types of information can be gained by involving different informant groups in research about the central person's experience. Primary guardians can provide information about interpreting central persons' indicators of expression and broad assessments of their personal life. Other adults can provide insight relative to the central person's capacities outside of the primary guardian-central person dyad. Peers can provide insight about personal characteristics (i.e., personality traits). Utilizing different data collection methods can foster manifest and latent content to emerge. Analyses and reflexivity which involve diverse perspectives are essential to ensure findings are grounded in lived experience and professional lenses. The method highlights the importance of furthering research to understand the experiences of individuals who cannot traditionally self-express, which may influence possibilities for enhancing care, participation opportunities, and overall well-being.